Immune : a journey into the mysterious system that keeps you alive - Dettmer, Philipp (New York : Random House, 2021)
"Although everyone who has ever had a cold is familiar with the human immune system and its importance, few understand just how complex and intricate the immune system is. In Immune, Internet creator and storyteller Philipp Dettmer takes readers on a journey through the fortress of the human body and its defenses. There is a constant battle raging just under our skin, full of stories of invasion, strategy, defeat, and noble self-sacrifice. In fact, in the time you've been reading this, your immune system has identified and eradicated multiple cancer cells that started to grow in your body. Enlivened by engaging full-color graphics and immersive descriptions, Immune turns one of the most intricate, interconnected, and pervasive subjects in biology--immunology--into a gripping adventure through an alien landscape. Touching on our body's defenses, the types of adversaries we face (including a chapter on the coronavirus), and the grave consequences of immune malfunction, Immune is a vital crash course in what is arguably, and increasingly, the most important system in the body"--
Includes bibliographical references (page 317) and index.
MNS
Keywords: Immune system; Immunology